Protecting the Community: Improving Knowledge, Attitude, and Behaviour towards Health Insurance - Erny Octaviany; Farah Rizqi; Annisa Ryan Susilaningrum; Firdaus Hafidz; Bagas Suryo Bintoro; Putri Tiara Rosha (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Indonesia has implemented the National Health Insurance (Jaminan Kesehatan Nasional/JKN) program administered by the Health Care and Social Security Agency (BPJS Kesehatan) to improve the quality of community health and well-being. National Health Insurance implementation has had many challenges in eight years, such as complicated registration, premiums, unsatisfactory services, and lack of community participation. Policies regarding JKN should be better known and understood. This study aimed to know the knowledge, attitudes, and behavior towards health insurance that will be useful for stakeholders to develop public policies. This study was conducted in Umbulsari B sub-village in Sumberharjo, Prambanan, Yogyakarta, the lowest area of JKN participation based on Sleman HDSS data. We used a cross-sectional study design among 91 respondents who filled out a paper sheet questionnaire that consisted of five sections: demographic characteristics and insurance participation, knowledge, attitudes, actions, and satisfaction with the JKN program; the community service activities; coordination with local stakeholders; JKN participation identification using CHIKA; and educational media production and publication. Local stakeholders said that awareness about JKN is low. The Chat Assistant JKN (CHIKA) data identification from 529 IDs showed that 78.1% had become JKN participants, and 73.3% were “active”. The respondents correctly answered most of each knowledge point (score >90%). However, there were several aspects that respondents disagreed with: “every participant will get the same health services (19.78%) in attitude points, and health workers in health facilities do not discriminate (21.21%) in satisfaction points. Additionally, 21.21% of respondents rarely use health services routinely for medical check-ups. We developed educational media about the importance of JKN, as well as using CHIKA and Pandawa tutorials. Education about health insurance needs to be done continuously according to the local cultural context and innovations so that the community remains protected from the financial burden of accessing health services.